2009
DOI: 10.1002/pros.21067
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among variant vascular endothelial growth factor (VEGF) and its receptor in relation to prostate cancer risk

Abstract: BACKGROUND Prostate cancer (PCa) incidence and mortality are disproportionately high among African-American (AA) men. Its detection and perhaps its disparities could be improved through the identification of genetic susceptibility biomarkers within essential biological pathways. Interactions among highly variant genes, central to angiogenesis, may modulate susceptibility for prostate cancer, as previous demonstrated. This study evaluates the interplay among three highly variant genes (i.e., IL-10, TGFβR-1, VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…As a result, there were 10 studies retrieved on the basis of the above search criteria for PCa susceptibility related to IL-10 À1082 A4G, À819 C4T and À592 C4A polymorphisms. 9,[16][17][18][19][20][21][22][23][24] The main study characteristics are summarized in Table 1. There were three studies of subjects of Asian descent 20,22,24 and seven studies of subjects of Caucasian descent.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, there were 10 studies retrieved on the basis of the above search criteria for PCa susceptibility related to IL-10 À1082 A4G, À819 C4T and À592 C4A polymorphisms. 9,[16][17][18][19][20][21][22][23][24] The main study characteristics are summarized in Table 1. There were three studies of subjects of Asian descent 20,22,24 and seven studies of subjects of Caucasian descent.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…There were three studies of subjects of Asian descent 20,22,24 and seven studies of subjects of Caucasian descent. 9,[16][17][18][19]21,23 Among these studies, three studies have investigated only one SNP (McCarron et al considered -1082 A4G; Eder et al considered -592 C4A; and Omrania et al considered À1082 A4G), whereas three studies included two SNPs (Michaud et al considered À1082 A4G and À819 C4T; Wang et al considered À1082 A4G and À592 C4A; and Kesarwani et al considered À1082 A4G and À819 C4T). The remaining four studies included three SNPs.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in BRCA1 carriers the low-VEGF T-allele confers protection from disease (Jakubowska et al 2008). Similarly, although large case-control studies have failed to find an association between prostate cancer risk and VEGF polymorphisms (Jacobs et al 2008), when gene-gene interactions are considered, several smaller studies have shown that VEGF polymorphisms can play a role in disease risk or aggressiveness (Sfar et al 2010; VanCleave et al 2010).…”
Section: Common Polymorphisms In Angiogenesismentioning
confidence: 99%
“…For example, the 2604C allele decreases transcriptional activity and protects against age-related macular degeneration (Galan et al 2010). In addition, there is evidence of genegene interactions with VEGF genotype ( VanCleave et al 2010). However, studies to identify VEGFR2 polymorphisms that might predict Lucentis response were negative (KloeckenerGruissem et al 2011).…”
Section: Vegfr2mentioning
confidence: 99%